THE COMPATIBILITY OF NEUTROPHIL TO LYMPHOCYTE COUNT RATIO WITH SERUM PROCALCITONIN AS BACTERIAL INFECTION MARKERS IN SEPSIS PATIENTS - Elvinawaty Elvinawaty; Hanifah Maani; Zelly Dia Rofinda; Husni Husni (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Bacterial infections and sepsis remain significant causes of morbidity and mortality in critical cases in Intensive Care Units (ICU) around the world. A quick and accurate diagnosis for sepsis is a challenge for clinicians and laboratory. The problem of an existing marker for sepsis with high sensitivity and specificity is still not satisfactory. Serum procalcitonin test is still widely used but cannot be supported by hospital laboratories especially in the regional public hospitals and needs more cost. Neutrophil-lymphocyte ratio is a potential index, easy, fast and cheap for bacteremia in patients with sepsis. This study aimed to determine the agreement of neutrophil-lymphocyte ratio with serum procalcitonin as a bacterial infection marker in sepsis patients. This study was an observational, analytical study with a cross-sectional design of 30 patients who had been diagnosed as sepsis by clinicians based on clinical signs of sepsis in the Intensive Care Unit of the Dr. M. Djamil Hospital Padang. The study was conducted from February to July 2016. Neutrophil and lymphocyte count was performed by flow cytometry method and procalcitonin test with Enzyme Linked Fluorescent Assay (ELFA). Results were analyzed by Kappa test with a statistical significance if p < 0.05. There were 30 subjects, consisting of 15 females (50%) and 15 males (50%) with the age mean of 48 years. Based on the Kappa test, the value obtained was kappa=0.634 (p=0.001) for the ratio neutrophil lymphocyte with procalcitonin. There was a substantial agreement between ratio neutrophil lymphocyte with procalcitonin test.